Soaking Soybean Seeds with Abeliophyllum distichum Nakai Extract Increased the Yield and Nutritional Value of Soybean Sprouts - Jeong-Ho Kim; Yong-Han Yoon; Sanjeev Kumar Dhungana; Il-Doo Kim; Dong-Hyun Shin (Polish Journal of Food and Nutrition Sciences)
Abeliophyllum distichum Nakai, an ornamental plant, contains a wide range of phytochemicals having pharmaceutical properties. The use of different plant-based extracts for the enhancement of yield and/or quality of soybean sprouts, one of the most inexpensive but nutritious food products, is common. The objective of this study was to examine the effect of A. distichum flower extract (ADE) on the yield and nutritional value of soybean sprouts. Soybean seeds were soaked in ADE solutions with concentrations ( w/v ) of 0.5% (ADE-0.5), 1% (ADE-1), 3% (ADE-3), and 5% (ADE-5). The effect of ADE concentration on the yield and different nutrient components varied. The highest soybean sprout yield and vitamin C content were found with ADE-3. The most abundant essential amino acid content was detected in ADE-1, whereas the greatest amounts of total isoflavones and total minerals were determined in ADE-5 and the ADE-untreated control, respectively. Overall results of yield, color, and contents of vitamin C, amino acids, and isoflavones suggest that 1% or 3% of A. distichum extract could be an optimum concentration to soak the soybean seeds for higher sprout yield and nutrient content.